Transcranial electrical stimulation of the prefrontal cortex to boost the hypnosis experience: who benefits most? - Perri, Rinaldo Livio; Di Filippo, Gloria (Frontiers in Psychology, 2023)
Many attempts have been made to enhance hypnotizability. The most recent studies adopted the non-invasive brain stimulation to deactivate the dorsolateral prefrontal cortex (DLPFC) during hypnosis, indicating this as a promising approach. However, it is still no clear whether individual factors can predict the effects of stimulation on hypnotizability. In the present study we adopted the Phenomenological Consciousness Inventory (PCI) to retrospectively assess the mental processes during hypnosis and to predict hypnotizability, here defined as "hypnoidal state". The aim was to investigate the possible role of the hypnotic susceptibility on the efficacy of a validated approach of hypnosis enhancement through cathodal transcranial electrical stimulation (tDCS) of the left DLPFC.Results indicated that the lower hypnoidal state at baseline predicted the greater enhancement after the active tDCS. These findings suggest the subjects with lower hypnotic responsiveness as the best candidates for the tDCS interventions of hypnosis enhancement, at least for the montage targeting the left DLPFC. Neurocognitive underpinnings and clinical implications of the results are discussed.